Expression and functional characterisation of natural R147W and K150del variants of protein C in the Chinese population - Ding, Qiulan; Yang, Likui; Hassanian, Seyed Mahdi; Rezaie, A R (Thrombosis and haemostasis, 2013)
Protein C is a vitamin K-dependent serine protease zymogen in plasma which upon activation to activated protein C (APC) by thrombin down-regulates the clotting cascade by limited proteolysis of the procoagulant cofactors Va and VIIIa. In addition to its anticoagulant activity, APC also exhibits potent cytoprotective and anti-inflammatory activities. While the anticoagulant activity of APC is enhanced by the cofactor function of protein S on membrane phospholipids, the cytoprotective intracellular signalling activity of APC requires complex formation with endothelial protein C receptor (EPCR) expressed on the vascular endothelium. Two natural variants of APC [Arg-147 to Trp substitution (R147W) and Lys-150 deletion (K150del)] have been identified in the Chinese population as hotspot mutants occurring with high frequencies of 27.8% and 13.9%, respectively, among 36 protein C-deficient subjects. The affected individuals exhibit variable thrombotic tendencies. To understand the underlying cause of the thrombotic phenotype in these patients, we expressed these two protein C variants in mammalian cells and characterised their anticoagulant and anti-inflammatory properties using established in vitro and cellular assays. Our results suggest that both R147W and K150del variants have normal amidolytic and proteolytic activities in the absence of cofactors. However, the R147W mutant exhibits ~3 times lower affinity for binding to EPCR and the K150del variant has ~2-3-fold impaired anticoagulant activity in the presence of protein S. These results provide some insight into the possible pathogenic mechanism of protein C deficiency in Chinese patients carrying these mutations.